(untitled) (Tamaddun, 2016)
The writer obtain data by direct observation and other books or documents are relevant with the culture in North Kalimantan. Through Semiotic approach, that was determined to use icon, index and simbol, we knew the purpose and the real meaning of Mandau and Sumpit in connection with life manner of Dayak tribe. The type of this research is purposive sampling and semiotic approach. Large samples are 5 types of Mandau and 14 type of Mandau Dance. The object of this research is the Dayak community and all assosiated with Mandau and Sumpit in Dayak. The result showed that mandau and sumpit is as objects of art and culture, souvenirs, goods collection and weapons to hunt, trim scrub and are also used as an instrument for farm and agricultural.